Effects of moisture content and fertilizer source on growth and yield of sweet corn - Sheikh Muhumed, Mohamed Abdirahman (2013)
Corn (Zea mays L.) is one of the most important cereal crops worldwide, next to wheat and rice. In Malaysia, corn can grow successfully as the climate of the country is suitable for the crop. However, it is a minor crop even though the demand for corn increases over the years. Corn is imported yearly to satisfy the country’s needs. The main challenges for corn production are low soil fertility, low pH and water shortage. Thus, to overcome these problems, two studies were conducted in a rain shelter at Field 2, Faculty of Agriculture,Universiti Putra Malaysia, Serdang, Malaysia. The objectives of first experiment were to determine the effect of soil moiture content and fertilizer sources on the growth and yield of sweet corn and to evaluate the effect of their interaction on the yield of the sweet corn. The treatments were four soil moiture contents (Smc) namely: 100% (Smc1), 90% (Smc2), 80% (Smc3), and 70% (Smc4), and four fertilizer sources namely: mineral fertilizer (NPK), goat manure (GM), poultry manure (PM) and without fertilizer (control). The treatments were arranged in split-plot design as the moisture content was assigned as main plot factor while fertilizer sources as sub plot factor. The results showed that the total dry matter (all above ground excluding yield) significantly (P<0.05) increased with the increase in soil moisture content. 100% soil moisture content (Smc1)) with goat manure (GM) gave higher biomass compared to PM and control treatment. Highest root dry weight was achieved from 90% soil moisture content (Smc2) with poulry manure (PM). In terms of yield components, interaction between soil moisture content and fertilizer sources significantly (P<0.05) affected the plant cob and ear weight. Both organic ( GM and PM) and inorganic (NPK) fertilizers enhanced cob and ear weight at Smc1 and Smc2 while NPK and GM gave higher grain weight at Smc1and Smc2 compared to PM and control treaments. Positive correlation between total dry matter, yield components and nutrient uptake was observed, indicating better crop response to soil moisture and fertilizer (organic and inorganic) application. The second experiment was conducted in Field 2 under rain shelter to evaluate the effect of soil moisture contents and inorganic fertilizer levels on the growth and yield performance of sweet corn and to determine the maximum NPK rate that would enhance high growth and yield of sweet corn. Three soil moisture contents and four fertilizer levels were used namely: 90% (Smc2), 80% (Smc3) and 70% (Smc4), while NPK fertilizer levels were: F1 (0:0:0 kg ha-1), F2 (60:30:45 kg ha-1), F3 (120:60:90 kg ha-1) and F4 (180:90:135 kg ha-1). The results showed that total dry matter yield significantly (P<0.05) increased with increase in soil moisture content. 90% (Smc2) treatments with 150% (F4) gave higher shoot dry weight compared to the other fertilizer levels. Soil moisture contents and fertilizer levels significantly (P<0.05) influenced the yield components. Ear,cob and grain weight were found to be higher in 100% smc1 with fertilizer level 150% (F4) of recommended rate. When fertilizer level was increased from 100% (F3) to 150% (F4) of recommended rate then ear (25%), cob (39%), and grain (23%) also increased. This study showed that N, P, K, Ca and Mg uptake by the root and shoots was enhanced as the fertilizer level increased. This indicates that corn responded to fertilizer application by increasing total dry weight as supported by positive correlation between total dry matter (root and shoot) and N, P, K, Ca and Mg uptake by the roots and shoots. In conclusion, the current study revealed that sweet corn water demand is absolutely high in which total dry matter and yield components increased with increase in soil moisture contents for both experiments. In terms of fertilizers, organic fertilizers enhanced crop biomass and yield components to a level which can be considered as an alternate to chemical fertilizer application. Finally, in terms of NPK fertilizer levels, the current recommended fertilizer rate is not enough and 150% (F4) seems to be the best choice as this study has shown.